Redescription of the cicada genus Pycna Amyot & Audinet-Serville, 1843 (Hemiptera: Cicadidae: Cicadinae: Platypleurini) with the formation of two new genera, one new species, one revised species status and twenty-four new combinations - Sanborn, Allen F. (Zootaxa, 2020)
A recent genetic analysis has shown that the genus Pycna Amyot & Audinet-Serville, 1843 is polyphyletic. New genera are proposed for the species that have been classified together in the genus previously but form distinct clades from the clade containing the true species of Pycna. Pycnoides n. gen. is described for the species inhabiting continental Africa. Pycna antinorii (Lethierry, 1881), Pycna baxteri Distant, 1914, Pycna becarrii (Lethierry, 1881), Pycna dolosa Boulard, 1975a, Pycna hecuba Distant, 1904b, Pycna moniquae Boulard, 2012, Pycna natalensis Distant, 1905b, Pycna neavei Distant, 1912b, Pycna passosdecarvalhoi Boulard, 1975b, Pycna quanza (Distant, 1899a), Pycna semiclara (Germar, 1834), Pycna sylvia (Distant, 1899b), Pycna umbelinae Boulard, 1975b, Pycna vitrea Schumacher, 1913, and Pycna vitticollis (Jacobi, 1904) are reassigned to Pycnoides n. gen. to become Pycnoides antinorii (Lethierry, 1881) n. comb., Pycnoides baxteri (Distant, 1914) n. comb., Pycnoides becarrii (Lethierry, 1881) n. comb., Pycnoides dolosa (Boulard, 1975a) n. comb., Pycnoides hecuba (Distant, 1904b) n. comb., Pycnoides moniquae (Boulard, 2012) n. comb., Pycnoides natalensis (Distant, 1905b) n. comb., Pycnoides neavei (Distant, 1912b) n. comb., Pycnoides passosdecarvalhoi (Boulard, 1975b) n. comb., Pycnoides quanza (Distant, 1899a) n. comb., Pycnoides semiclara (Germar, 1834) n. comb., Pycnoides sylvia (Distant, 1899b) n. comb., Pycnoides umbelinae (Boulard, 1975b) n. comb., Pycnoides vitrea (Schumacher, 1913) n. comb., and Pycnoides vitticollis (Jacobi, 1904) n. comb. Pycnoides zambiaensis n. sp. is described as new to increase the diversity of the new genus further and represents the first record of a species in the group for Zambia. Eopycna n. gen. is described for the Asian species previously assigned to Pycna. Pycna coelestia Distant, 1904a, Pycna concinna Boulard, 2005, Pycna himalayana (Naruse, 1977), Pycna indochinensis Distant, 1913, Pycna minor Liu, 1940, Pycna montana Hayashi, 1978, Pycna repanda (Linnaeus, 1758), and Pycna verna Hayashi, 1982 are reassigned to Eopycna n. gen. to become Eopycna coelestia (Distant, 1904a) n. comb., Eopycna concinna (Boulard, 2005) n. comb., Eopycna himalayana (Naruse, 1977) n. comb., Eopycna indochinensis (Distant, 1913) n. comb., Eopycna minor (Liu, 1940) n. comb., Eopycna montana (Hayashi, 1978) n. comb., Eopycna repanda (Linnaeus, 1758) n. comb., and Eopycna verna (Hayashi, 1982) n. comb. Pycna angusta (Butler, 1882) rev. stat. is removed from junior synonymy of Pycna madagascarensis (Distant, 1881). Pycna schmitzi Boulard, 1979 is reassigned to Canualna Boulard, 1985a to become Canualna schmitzi (Boulard, 1979) n. comb. and Pynca tangana (Strand, 1910) is reassigned to Orapa Distant, 1905c to become Orapa tangana (Strand, 1910) n. comb.